Effects of Purified Salvia miltiorrhiza Extract on Cardiac Vascular Smooth Muscle Hypoxic Cells - Begum Husna; Todd On; Yi Zhun Zhu (Elsevier, 2007)
Recently, we have reported that purified Salvia miltiorrhiza extract (PSME) could prevent myocardial infarction in vivo and myocardial ischemia/reperfusion injury in isolated rat hearts (ex vivo). The aim of this project is to determine whether PSME exerts any cardioprotective effects in vitro. The vascular smooth muscle cell line was used and the effects of the drugs were determined after inducing hypoxia. Gene expression levels of the pro-apoptotic genes Asp53, Bax, and Fas were significantly down-regulated by 0.78-, 0.82-, and 0.87-fold, respectively, and Bcl-2 was up-regulated by 0.82-fold in the PSME-treated groups as compared to the hypoxic group (P<0.05). Significant reduction in immunoreactivity of the protein products of these genes as well as least nuclear green fluorescence observed in TUNEL staining indicate the therapeutic potential of this drug. Furthermore, cardiac antioxidant enzymes assay confirmed this deduction as PSME had slight preserving effects on superoxide dismutase and catalase (0.25 ± 0.01 vs 0.488 ± 0.02 units/mg protein and 0.026 ± 0.012 vs 0.076 ± 0.01 µmol per min per mg protein, respectively; each P<0.05). No significant results were obtained with glutathione S-transferase and GSH peroxidase antioxidant tests. Our results demonstrated that PSME exerts antioxidant effects in vitro, indicating the therapeutic potential of this drug. Keywords:: ischemic myocardium, purified Salvia miltiorrhiza extract, hypoxia